Answer:
x - 6.
Step-by-step explanation:
3(x-6) = 3x -18
3x -18 + 4x + 12 -6x = x - 6
The simplified version of this would be: (4x+16y)+(12x+3y). You then combine like terms (4x+12x=16x) and (16y+3y=19y). Since this is the most simplified you can make the equation THE ANSWER would be 16x+19y
Answer:
Step-by-step explanation:
Given that a poll showed the approval rating to be 0.45 (45 %)
Second poll n =2500: sample p = 1185/2500 = 0.474
H0: p = 0.45
Ha: p not equals 0.45
(Two tailed test)
p difference = 0.024
z-statistic 0.179
Significance level P = 0.8577
95% CI of observed proportion 0.24% to 0.83%
Since p>0.05 we accept null hypothesis
The results of the second poll do not indicate that the proportion of voters who approve of the job the president is doing is significantly higher than the original level